1990
DOI: 10.1016/0040-1951(90)90146-y
|View full text |Cite
|
Sign up to set email alerts
|

Pre-folding magnetization reconfirmed for the Late Ordovician-Early Silurian Dunn Point volcanics, Nova Scotia

Abstract: Paleomagnetic results have been obtained for three new sites in steeply inclined subarea1 volcanic flows of the Dunn Point Formation from the Avalon terrane of Nova Scotia. Demagnetization analysis reveals a characteristic magnetization, carried by hematite, which is similar to that reported in previous studies of this unit. A new and improved fold test for the characteristic component, combining paleomagnetic and structural data from the present study with paleomagnetic data for vertically dipping flows (and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…These results are in agreement with palaeomagnetic results from previous studies of the Springdale Group (Potts, van der Pluijm & Van der Voo 1993a) and other Silurian redbeds of Newfoundland (Lapointe 1979;Buchan & Hodych 1989 Pluijm & Van der Voo 1993b) but are significantly different from coeval volcanic rocks from Newfoundland (Potts et al 1993a;Gales, van der Pluijm & Van der Voo 1989;Lapointe 1979) as well as volcanics from Nova Scotia (Van der Voo & Johnson 1985;Johnson & Van der Voo 1990), that indicate much higher southerly palaeolatitudes at this time. Discrepancies in palaeolatitudes determined from coeval sedimentary and volcanic rocks are not unique to Newfoundland.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…These results are in agreement with palaeomagnetic results from previous studies of the Springdale Group (Potts, van der Pluijm & Van der Voo 1993a) and other Silurian redbeds of Newfoundland (Lapointe 1979;Buchan & Hodych 1989 Pluijm & Van der Voo 1993b) but are significantly different from coeval volcanic rocks from Newfoundland (Potts et al 1993a;Gales, van der Pluijm & Van der Voo 1989;Lapointe 1979) as well as volcanics from Nova Scotia (Van der Voo & Johnson 1985;Johnson & Van der Voo 1990), that indicate much higher southerly palaeolatitudes at this time. Discrepancies in palaeolatitudes determined from coeval sedimentary and volcanic rocks are not unique to Newfoundland.…”
supporting
confidence: 91%
“…When the correct values for bedding are used, the magnetization predates folding. The matter can only be considered controversial if it is shown that the actual bedding attitudes are different from those so carefully measured by Johnson & Van der Voo (1990). To our knowledge such 'errors' have not been demonstrated.…”
Section: Implications For a P P A R E N T Polar W A N D E Rmentioning
confidence: 87%
See 1 more Smart Citation
“…It moved to reside at high southerly latitudes (60°-54°) near Gondwana during the Cambrian Hodych and Buchan 1998;Mac Niocaill 2000). During the Floian, Avalonia moved rapidly north to intermediate (41 ± 8°S) latitudes indicating increasing separation from Gondwana concurrent with a decrease in the separation between Avalonia and Laurentia (Johnson and Van der Voo 1990;Hodych et al 2004;Hamilton and Murphy 2004). Comparable faunal assemblages support Gondwanan linkages for Avalonia until the Tremadoc (Cocks et al 1997;Fortey and Cocks 2003); after which, the faunal provinciality indicates changing affinities from Gondwanan to genera with Laurentian ancestors.…”
Section: Time Of Riftingmentioning
confidence: 92%
“…w. Johnson and Van der Voo (1985), x Thompson et al (2010),. y Johnson and Van Der Voo (1990),. z Hamilton and Murphy (2004),.…”
mentioning
confidence: 98%